2007
DOI: 10.1128/jb.00530-07
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Activation by the DNA-Binding Domain of the AraC Family Protein RhaS in the Absence of Its Effector-Binding Domain

Abstract: The Escherichia coli L-rhamnose-responsive transcription activators RhaS and RhaR both consist of two domains, a C-terminal DNA-binding domain and an N-terminal dimerization domain. Both function as dimers and only activate transcription in the presence of L-rhamnose. Here, we examined the ability of the DNAbinding domains of RhaS (RhaS-CTD) and RhaR (RhaR-CTD) to bind to DNA and activate transcription. RhaS-CTD and RhaR-CTD were both shown by DNase I footprinting to be capable of binding specifically to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 51 publications
(66 reference statements)
1
32
0
Order By: Relevance
“…Given that full-length RhaS protein severely aggregates when overexpressed, we used the purified C-terminal DNA binding domain of RhaS [His6-RhaS(163-278), previously called His6-RhaS-CTD (34)] for these assays. His6-RhaS(163-278) was previously found capable of in vitro DNA binding and transcription activation (34). Using electrophoretic mobility shift assays, we found that His6-RhaS(163-278) was able to bind in vitro to DNA fragments carrying each of the RhaR half sites at rhaSR, although 3-to 10-fold less tightly than to the RhaS half sites at rhaBAD (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Given that full-length RhaS protein severely aggregates when overexpressed, we used the purified C-terminal DNA binding domain of RhaS [His6-RhaS(163-278), previously called His6-RhaS-CTD (34)] for these assays. His6-RhaS(163-278) was previously found capable of in vitro DNA binding and transcription activation (34). Using electrophoretic mobility shift assays, we found that His6-RhaS(163-278) was able to bind in vitro to DNA fragments carrying each of the RhaR half sites at rhaSR, although 3-to 10-fold less tightly than to the RhaS half sites at rhaBAD (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…To further test this hypothesis, we assayed a fusion with an upstream endpoint at Ϫ312 and carrying point mutations at three consensus positions in the CRP binding site ( Fig. 1) that we previously found greatly reduced CRP coactivation of rhaSR (34). We found that the CRP binding site point mutations reduced RhaS repression of the ⌬312 fusion by more than sixfold to a level similar to that of the ⌬114 fusion (Table 1, ⌬312 CRP Ϫ ).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations